Towards integrating climate security in the National Climate Change Action Plan (NCCAP) 2023-2027 - Kenduiywo, Benson Kipkemboi; Korir, Victor Kipkurui; Chepngetich, Brenda (2023)
The UNDP & Life Peace Institute (LPI) report on mapping climate security adaptations highlights that the link between climate and conflict depends on the interplay of exposure to climate hazards, vulnerability, and coping capacity of states and communities. Therefore, due increasing impacts of Climate Change (CC), it is crucial for the Kenyan governments to identify and mitigate climate security1 risks both at national and county levels. The National Climate Action Plan (NCCAP) outlines the Kenyan government’s strategy on mitigation and adaptation to climate change and its effects. With the expiry of the 2017–2022 NCCAP, preparation of a new plan is underway based on the current climate change challenges and lessons learnt from the previous NCCAP phase. One of the issues that stood out in the 2017–2022 NCCAP was the omission of climate security strategies. In this regard, a workshop was co-organized by the Alliance of Bioversity International and CIAT (ABC) and Kenya Red Cross Society at Panari Hotel, Nairobi from 24th — 25th July 2023 to integrate Climate Security. The workshop participants comprised of takeholders drawn from various sectors including government ministries, research organizations, humanitarian organizations, and local and regional economic blocs.